Unravelling tectonic and lithological effects on transient landscapes in the Gulf of Corinth, Greece - Zhou,Z; Whittaker,A; Bell,R; Hampson,G (Basin Research, 2024)
Landscapes are the integrated product of external forcings (e.g. tectonics and climate) and intrinsic characteristics (e.g. bedrock erodibility). In principle, hardbedrock with low erodibility can steepen rivers in a similar way to tectonic uplift. A key challenge in geomorphic analysis is thus separating the tectonic and lithologicaleffects on landscapes. To address this, we focus on multiple rivers that are transiently incising through contrasting lithologies in the Gulf of Corinth, Greece,where tectonic history is broadly well constrained. We first exploit topographic metrics and river long profiles to demonstrate that landscapes are responding to both tectonics and lithology. In particular, the long profiles are divided into knickpoint-bounded segments, and at this scale, channel steepness is shown to be more sensitive to lithology than the entire catchment, possibly due to relatively uniform erosion rate at the segment scale. We then use segment-scale steepness variations between different lithologies to constrain their relative erodibilities(Klime:Kcong.:Ksand-silt: Kp-con sed. = 1:2:3:4), which are further converted into actual lithology-dependent erodibilities by modelling a well-constrained, ca. 700 kaknickpoint in the Vouraikos catchment. The effectiveness of lithology-dependent erodibilities is supported by the observation that if lithology-dependent erodibilitiesare used to calibrate studied river long profiles in χ distance, we obtain long profile concavities that fall within the theoretical range. Finally, we use lithology-calibrated metrics to provide new geomorphic constraints on the timing and magnitude of tectonic perturbations in these catchments. These geomorphic results are interpreted in conjunction with previous onshore and offshore studies to shed new light on fault growth and linkage history in the Gulf of Corinth. Our study therefore provides a topographic analysis-based approach to quantify lithological effects on transient catchments